2021
DOI: 10.1542/peds.2020-042762
|View full text |Cite
|
Sign up to set email alerts
|

A Waitlist Intervention for Transgender Young People and Psychosocial Outcomes

Abstract: BACKGROUND: Recent referrals of transgender young people to specialist gender services worldwide have risen exponentially, resulting in wait times of 1-2 years. To manage this demand, we introduced an innovative First Assessment Single-Session Triage (FASST) clinic that provides information and support to young people and their families and triages them onto a secondary waitlist for subsequent multidisciplinary care. Although FASST has been shown to substantially reduce initial wait times, its clinical impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 16 publications
2
59
0
Order By: Relevance
“…Furthermore, the suicidality of GD youth presenting at CAGCs, while markedly higher than non-referred samples, has been reported to be relatively similar to that of youth referred to generic child and adolescent mental health services (Carmichael, 2017 ; de Graaf et al, 2022 ; Levine et al, 2022 ). A recent study reported that 13.4% of one large gender clinic’s referrals were assessed as high suicide risk (Dahlgren Allen et al, 2021 ). This is much less than conveyed by the often cited 50% suicide attempt figure for trans youth (Tollit et al, 2019 ).…”
Section: Gender-affirming Treatment For Youth With Gender Dysphoria: ...mentioning
confidence: 99%
“…Furthermore, the suicidality of GD youth presenting at CAGCs, while markedly higher than non-referred samples, has been reported to be relatively similar to that of youth referred to generic child and adolescent mental health services (Carmichael, 2017 ; de Graaf et al, 2022 ; Levine et al, 2022 ). A recent study reported that 13.4% of one large gender clinic’s referrals were assessed as high suicide risk (Dahlgren Allen et al, 2021 ). This is much less than conveyed by the often cited 50% suicide attempt figure for trans youth (Tollit et al, 2019 ).…”
Section: Gender-affirming Treatment For Youth With Gender Dysphoria: ...mentioning
confidence: 99%
“…To investigate whether waiting could be more of a positive experience, researchers in Australia trialled the First Assessment Single-Session Triage (FASST) clinic [ 25 ]. The FASST was found to be successful in its aims “to decrease wait time into the service, provide initial assessment and triage, and deliver information, education and support to patients who5are TGD and their families” [ 25 ] (p. 2). Young people who were able to access FASST showed an “increased sense of agency, contributed to by changes to outlook, validation, sense of self, and confidence” [ 25 ] (p. 7).…”
Section: Discussionmentioning
confidence: 99%
“…The FASST was found to be successful in its aims “to decrease wait time into the service, provide initial assessment and triage, and deliver information, education and support to patients who5are TGD and their families” [ 25 ] (p. 2). Young people who were able to access FASST showed an “increased sense of agency, contributed to by changes to outlook, validation, sense of self, and confidence” [ 25 ] (p. 7). In addition, Mulcahy and colleagues [ 6 ] highlighted the positive interactions many of their participants had with a cancer support group as a source of knowledge and comfort.…”
Section: Discussionmentioning
confidence: 99%
“…These decisions have been partly determined by the long waiting lists. In some countries the waiting times for specialised gender clinics are now up to three to five years, 13 14 15 making it necessary to rethink the organisation of care. 15 Our centre in Ghent, Belgium, for example, saw 487 patients for an initial appointment in 2021.…”
Section: Getting Startedmentioning
confidence: 99%
“…In some countries the waiting times for specialised gender clinics are now up to three to five years, 13 14 15 making it necessary to rethink the organisation of care. 15 Our centre in Ghent, Belgium, for example, saw 487 patients for an initial appointment in 2021. But a further 863 people contacted our service (an increase of 170% compared with 2016) and had to be put on the waiting list.…”
Section: Getting Startedmentioning
confidence: 99%